2020
DOI: 10.21873/anticanres.14062
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Infusion Reactions to and Infusion Rate of Monoclonal Antibodies Used in Cancer Treatment

Abstract: Background: Patients with cancer who are treated with monoclonal antibodies are at risk for developing infusion reactions. However, for some monoclonal antibodies, the incidence of infusion reactions is low or can be lowered by the use of adequate premedication schedules. It is often feasible to increase the infusion rate/lower the post-administration observation time. This review gives an overview of infusion reactions and the possibility of accelerating infusion rates. Materials and Methods: Data on infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 46 publications
1
61
0
Order By: Relevance
“…In accordance with earlier studies, 18,36,37 the pooled rates demonstrated that infusion-related AEs, and infections were common, which might spring from the release of cytokines and/or other chemical mediators, 36 and the decreased immunoglobulin levels, 37 respectively. However, the rates of patients with infusion-related AEs and any infections were numerically higher, 11,37 and the infections mainly occurred in pulmonary and urinary, but did not present as herpetic rashes or tuberculosis reactivation when compared with the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with earlier studies, 18,36,37 the pooled rates demonstrated that infusion-related AEs, and infections were common, which might spring from the release of cytokines and/or other chemical mediators, 36 and the decreased immunoglobulin levels, 37 respectively. However, the rates of patients with infusion-related AEs and any infections were numerically higher, 11,37 and the infections mainly occurred in pulmonary and urinary, but did not present as herpetic rashes or tuberculosis reactivation when compared with the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Although DEX was not used as premedication, the incidence of IRRs in the REGARD trial was lower than in the RAINBOW and RAISE trials. DEX and H 1 AT are generally used as anti-allergy premedication (1,5). However, the benefits of these drug combination are unknown, and suitable doses are not well established.…”
Section: Discussionmentioning
confidence: 99%
“…anticancer agents, mAbs may cause infusion-related reactions (IRRs) (1)(2)(3). Most IRRs are mild with symptoms such as chills, fever, nausea, skin rash, and pruritus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is easy to relapse after these treatments, and the patients' survival rates are not significantly improved. Immunotherapy is useful for treating tumors, the mAbs bevacizumab, rituximab, and trastuzumab were already widely used against tumors outside the brain (75)(76)(77)(78)(79). But the current immunotherapy for medical glioma is costly and inefficient.…”
Section: The Application Of Phage Nanomaterials To Glioma Therapymentioning
confidence: 99%